Comparative Analysis Of E-Learning Companies - Chee, Chan Huan (2002)
In this paper , the author would like to generate an effective e-learning software comparative analysis for the use of corporate company. E-learning is now a new technology and the software also can be named as 'new product' in the world marketplace.